The investigation of the peculiarities of completing the machine milking of high-yielding cows on industrial type complexes - Paliy, A. P.; Ishchenko , K. V. (Scientific Progress & Innovations, 2019)
The purpose of the article is studying the technological peculiarities of completing the machine milking of high-yielding cows on milking installations at different time of delaying milking machines removal. Methods of the research. Scientific experiments were conducted on modern milking machines of the “Parallel” type of “Bou Matic” firm, in which the final operations of machine after-milking and removing teat cups are carried out by using a pneumatic machine and a manipulator. The scientific-economic experiment was conducted by the method of periods on 3 groups of Ukrainian black-and-white milk breed analogues, 15 heads in each to determine the degree of the delay influence in removing the milking machine from the udder of high-yielding cows after the finishing machine milking on the milk ejection indices and the cows’ health condition. The research results. According to the results of analyzing milk ejection indices of high-yielding cows with the delay of removing the milking machine from the udder after finishing the milking process (the delay time was 8, 12 and 15 seconds) it was established that they did not have any sufficient differences. At the same time, the operator spent more time on milking cows with the delay of 15 seconds, but the amount of the obtained milk in the first minute of milking tended to decrease in the cows with the delay of 8 seconds, and the amount of milk during hand after-milking was 0.10 kg in comparison with 0.07–0.09 kg, with the delay of removing the machine, correspondingly, by 12 and 15 seconds. The elements of scientific novelty. New data on influencing the technological methods of completing the machine milking of high-yielding cows on milking installations in the conditions of industrial complexes on reducing cow's udder injuries, increasing the intensity and completeness of milking, and raising the labor productivity of the machine milking operator have been received. Practical significance. Based on the research, the feasibility of using technical- technological solutions for milking of high-yielding cows, which have no negative impact on animals, has been experimentally substantiated. Such solutions ensure high rates of milk ejection and obtaining higher-quality products.